WALLABY early science – III. An H i study of the spiral galaxy NGC 1566. Issue 2 (27th May 2019) - Elagali, A; Staveley-Smith, L; Rhee, J; Wong, O I; Bosma, A; Westmeier, T; Koribalski, B S; Heald, G; For, B-Q; Kleiner, D; Lee-Waddell, K; Madrid, J P; et al.
ABSTRACT: This paper reports on the atomic hydrogen gas (H i ) observations of the spiral galaxy NGC 1566 using the newly commissioned Australian Square Kilometre Array Pathfinder radio telescope. We measure an integrated H i flux density of$180.2$ Jy km s −1 emanating from this galaxy, which translates to an H i mass of$1.94× 10^{10}\, M_{\odot }$ at an assumed distance of$21.3$ Mpc. Our observations show that NGC 1566 has an asymmetric and mildly warped H i disc. The H i -to-stellar mass fraction (M$_{\rm{H\, {{\small I}}}}$ /M∗ ) of NGC 1566 is 0.29, which is high in comparison with galaxies that have the same stellar mass ($10^{10.8}$ M⊙ ). We also derive the rotation curve of this galaxy to a radius of$50$ kpc and fit different mass models to it. The NFW, Burkert, and pseudo-isothermal dark matter halo profiles fit the observed rotation curve reasonably well and recover dark matter fractions of 0.62, 0.58, and 0.66, respectively. Down to the column density sensitivity of our observations ($N_{\rm{H\, {{\small I}}}}\, =\, 3.7× 10^{19}$ cm −2 ), we detect no H i clouds connected to, or in the nearby vicinity of, the H i disc of NGC 1566 nor nearby interacting systems. We conclude that, based on a simple analytic model, ram pressure interactions with the IGM can affect the H i disc of NGC 1566 and is possibly the reason for the asymmetries seen in the H i morphology of NGC 1566.